PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 007 SUNGAI KUBU KECAMATAN KUBU KABUPATEN ROKAN HILIR - Sriwati '; Lazim N '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is motivated by lowyields social studies students, with agrade average of 68.83. While the completeness criteria Minimum value (KKM)IPS is 65 Among students who were 30 only 15 students who achieve KKM withclassical completeness 50%. This research is Classroom Action Research (CAR)conducted aiming to improve science learning outcomes Elementary Schoolfourth grade students 007 Kubu River by implementing cooperative learningmodel TSTS. Data collection instruments in this thesis is the sheet activities ofteachers and students and learning outcomes. This thesis presents the resultsobtained by studying the average learning outcome measures 68.83 before rising12.84% to 77.67 in cycle I. In the second cycle increased by 17.20% to an averageof 80.67. activities of teachers in the first cycle the first meeting of the percentageobtained 55% with unfavorable category, the second meeting had become62.50%. Furthermore, the first meeting of the second cycle activity scoreincreased by 87.50% of teachers either category, at the second meeting increasedto 100% with a very good category. The results of the data analysis of studentactivity in the first cycle to 50% with the category is not very good, at the secondmeeting of 57.50% In this cycle students already understand the application ofcooperative learning activities with the type TSTS. And the second cycle activityscore of 77.50% of students increased with both categories. At the second meetingincreased to 97.50% with very good category. The results of the study at 007River Elementary School fourth grade faction proved that the application ofcooperative learning model to improve learning outcomes NHT IPS 007 fourthgrade students of SDN Sungai Kubu.Keywords: Cooperative Type TSTS, IPS leaning outcome